Effects of dried distillers grains with solubles and corn gluten feed on the overall growth and economic cos of growing Boer-type goats - Northcutt, Megan E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
This study was conducted to determine how substituting distiller’s dried grains with solubles (DDGS) and corn gluten feed (CGF) for soybean meal (SBM) could affect the growth of Boer-type goats, along with the possible economic benefit of using a cheaper product such as DDGS and CGF. To determine this we measured BW gain from day 0 – 35, ADG, ADFI, G:F, feed cost ($/kg of feed), feed cost/goat, feed cost/kg of gain. For this study, we used 75 Boer-type goats (29.6 ± 0.02 kg, approximately 70 d of age) in a completely randomized design, with the pen as the experimental unit, with 3 goats per pen, and 5 pens per treatment. The research was conducted for 35 d and all diets fed were isocaloric and isonitrogenous but varied in protein source. The 5 different treatments were different combinations of SBM, DDGS, and CGF including: 1) 100% SBM, 2) 100% DDGS, 3) 66% DDGS/33% CGF, 4) 33% DDGS/66% CGF, 5) 100% CGF. Data was analyzed using the GLIMMIX procedure of SAS with a 0.05 alpha value. After conducting this study, we found that there was no statistical significance for overall growth. The only significant differences were feed cost/goat (P = 0.0008) and a quadratic decrease (P = 0.049), and there was also a quadratic effect (P =0 .038) in ADFI. We came to the conclusion that 66% DDGS/33% CGF was the cheapest diet when looking purely at cost and not gain, but when considering both efficiency and economics, or the cost for each kg of weight gain, we found that 100% DDGS was the least expensive diet to use for growth in boer-type goats. In summary, this study proved that DDGS and CGF can be a successful substitution for SBM.
Keywords: Spring 2019